Preoperative Left Ventricular Energy Loss in the Operating Theater Reflects Subjective Symptoms in Chronic Aortic Regurgitation - Kainuma, Atsushi; Itatani, Keiichi; Akiyama, Koichi; Naito, Yoshifumi; Ishii, Maki; Shimizu, Masaru; Ohara, Junya; Nakamura, Naotoshi; Nakajima, Yasufumi; Numata, Satoshi; Yaku, Hitoshi; Sawa, Teiji (Frontiers in Surgery, 2022)
Background: There is currently no subjective, definitive evaluation method for therapeutic indication other than symptoms in aortic regurgitation. Energy loss, a novel parameter of cardiac workload, can be visualized and quantified using echocardiography vector flow mapping. The purpose of the present study was to evaluate whether energy loss in patients with chronic aortic regurgitation can quantify their subjective symptoms more clearly than other conventional metrics. Methods: We studied 15 patients undergoing elective aortic valve surgery for aortic regurgitation. We divided the patients into symptomatic and asymptomatic groups using their admission records. We analyzed the mean energy loss in one cardiac cycle using transesophageal echocardiography during the preoperative period. The relationships between symptoms, energy loss, and other conventional metrics were statistically analyzed. Results: There were seven and eight patients in the symptomatic and asymptomatic groups, respectively. The mean energy loss of one cardiac cycle was higher in the symptomatic group (121 mW/m [96 to 184]) than in the asymptomatic group (87 mW/m [80 to 103]) (p=0.040), whereas the diastolic diameter was higher in the asymptomatic group (65 mm [59 to 78]) than in the symptomatic group (57 mm [51 to 57]) (p=0.040). There was no significant difference between the symptomatic and asymptomatic groups in terms of other conventional metrics. Conclusions: An energy loss can quantify patients’ subjective symptoms more clearly than other conventional metrics. The small sample size is the primary limitation of our study, further studies assessing larger cohort of patients are warranted to validate our findings.